Mendelian randomization analysis reveals causal effects of migraine and its subtypes on early-onset ischemic stroke risk - Rui Zhang; Peng-Peng Niu; Shuo Li; Yu-Sheng Li (Scientific Reports)
Abstract Previous observational studies have suggested at a potential link between migraine, particularly migraine with aura, and the susceptibility to early-onset ischemic stroke. We aimed to investigate the causal effects of genetically determined migraine and its subtypes on the risk of early-onset ischemic stroke using the two-sample Mendelian randomization method. Genetic instrumental variables associated with migraine and its subtypes were acquired from two sources with the largest sample sizes available. Summary data for early-onset ischemic stroke was acquired from a study encompassing individuals aged 18–59 years, comprising 16,730 cases and 599,237 non-stroke controls. The random-effects inverse variance weighted method was used as the primary analysis approach. Additionally, linkage disequilibrium score regression analysis was used to evaluate the genetic correlation. The Mendelian randomization analysis revealed no association between overall migraine and migraine without aura with the risk of early-onset ischemic stroke. However, migraine with aura showed a suggestive association with an elevated risk of early-onset ischemic stroke, with odds ratios of 1.114 (95% confidence interval = 1.005 to 1.236, p-value = 0.040) and 1.062 (95% confidence interval = 1.002 to 1.126, p-value = 0.042) based on instruments from two independent sources. The odds ratio was 1.074 (95% confidence interval = 1.022 to 1.130, p-value = 0.005) based on instruments from both two sources. No evidence of heterogeneity or horizontal pleiotropy was found. By contrast, migraine with aura was not related to ischemic stroke in all adults. Furthermore, a significant positive genetic correlation was found between migraine with aura and early-onset ischemic stroke (genetic correlation = 0.208, 95% confidence interval = 0.038 to 0.377, p-value = 0.016). This study provides evidence of a causal relationship between migraine with aura and the risk of early-onset ischemic stroke, as well as a positive genetic correlation between them.